DINAMIKA PEMBAHASAN DAN PENGESAHAN RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) POVINSI RIAU TAHUN 2014-2019 - Putri, Azura Handayani; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The process of discussion and legalization of medium term development planing at Riau Province 2014-2019 has a lot of dynamic. This dynamic and legalization occurred at the Government of province Riau and the level of house of district representative ot Riau Province. Observing this, it is interesting to conduct this research. Based on this research there are something obtained : first, in the phase of discussion and legalization of medium term development planning at riau province there are 6 phase : arrangement of medium term development planning, initial planing of medium term development planning, planing of medium term development planning, final planning of medium term development planning, determination of medium term development planning, on the phase of legislative level consist of dynamic of mechanism discussion that has passed and unrelevance of medium term development planning draft to findings of particular comitee report. Second, based on the research it is concluded that the process of discussion ang legalization of medium term development planning has not been automatically implemented with the legalized mechanism. In essence, the discussion and legalization of medium term development planning it should have been relevant to the regulation and mechanism that has been determined, as a result it brings about interrity value and consolidation among fraction.Keywords : dynamic, medium term development planning, Riau Province